2009
DOI: 10.1095/biolreprod.108.069021
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression Levels of Genes Relating to the Ovulation Rate of the Yunling Black Goat1

Abstract: This study investigated the nucleotide sequences and tissue expression levels of genes relating to the ovulation rate in Yunling black goats, a famous Yunnan province, China, local breed with low fecundity. Five genes, FSHB, FSHR, BMP15, BMPR1B, and ESR2, were investigated; the complete cDNA sequences of these genes were 390, 2088, 1185, 1509, and 1585 bp, respectively, and compared with Boer goats (a more fecund breed), the sequence identities were 99%, 99%, 99%, 100%, and 99%, respectively. There were two ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 40 publications
5
44
1
Order By: Relevance
“…This symbolizes that non-synonymous sites evolved faster than the synonymous sites and positive selection effect over-shadows purifying selection. It is an implication that balancing selection (or positive Darwinian section) favoured new variants and increased allelic polymorphism [22] which in turn might induce a change in the conformation of protein structure, thereby affecting the signaling pathway during follicle differentiation and ovulation [23]. The 0.97 omega value of sheep observed in this study, signifies purifying selection i.e.…”
Section: Discussionmentioning
confidence: 64%
“…This symbolizes that non-synonymous sites evolved faster than the synonymous sites and positive selection effect over-shadows purifying selection. It is an implication that balancing selection (or positive Darwinian section) favoured new variants and increased allelic polymorphism [22] which in turn might induce a change in the conformation of protein structure, thereby affecting the signaling pathway during follicle differentiation and ovulation [23]. The 0.97 omega value of sheep observed in this study, signifies purifying selection i.e.…”
Section: Discussionmentioning
confidence: 64%
“…Consistent with the classic roles of FSH in steroidogenesis ( 19 ), Fshr is mainly expressed in the reproductive system (13)(14)(15)(16)(17). The receptor is also expressed in some nonreproductive organs and tissues ( 18,20 ) where it plays roles in regulating the development of the skeletal system and others (21)(22)(23)(24).…”
Section: Rt-pcrmentioning
confidence: 70%
“…Therefore, understanding the molecular mechanisms underlying such complex trait formation combined with functional gene discovery may provide valuable information for the breeder. FSH is a glycoprotein hormone mainly secreted by the pituitary gland to regulate gonadal development and function after delivery through the bloodstream (Meduri et al, 2002;Patsoula et al, 2003;Cui et al, 2009). Researchers have found that FSH can increase lipid accumulation in chicken abdominal fat by about 50% (Cui et al, 2012).…”
Section: Discussionmentioning
confidence: 99%